Consequences And Resolutions Of The Ms Glow Vs Ps Glow Trade Brand Dispute: Study Of Decision Number 2/Pdt.Sus.Hki/Merek/2022/Pn Niaga Sby Jo. MA Decision Number 161 K/Pdt.Sus-Hki/2023 - Sifa, Sifa Fauziah (Supremasi Hukum: Jurnal Penelitian Hukum, 2024)
Trademarks are in the form of images, logos, names, words, letters, numbers, color schemes, two and/or three dimensions, sounds, holograms, or a combination of them. The above factors are to distinguish goods and/or services produced by individuals or legal entities in order to trade goods and/or services. The existence of the trademark system aims to prevent the occurrence of trademark disputes between trademark owners. This study aims to explain the settlement of trademark disputes analyze the legal consequences of the decision number 2/Pdt.Sus.HKI/Merek/2022/PN Niaga Sby Jo. Supreme Court Decision Number 161 K/Pdt.sus-HKI/2023. The type of research used is normative juridical research and uses qualitative data analysis techniques to interpret research findings based on research data and implications obtained from relevant literature, laws and regulations, documents, books, and other library materials, as well as the author's research questions. In this research, the author explains that a mark can be said to have similarities in principle with other marks when the general public cannot be distinguished due to similarities in appearance, letters, numbers, colors, smell and pronunciation. Similarity of marks basically has a very close relationship with malice. Protect marks from inherently egalitarian and malicious business actors. The rise of trademark disputes in Indonesia, in the process of trademark registration, Indonesia applies the first to file principle, that is, trademark registration is only granted to businesses that first register their trademarks, and the state does not register/approve the registration of trademarks that are similar to the first registered trademark to others. On other similar products/services.